2016
DOI: 10.4172/2469-4134.1000170
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Suitable Land for Green Gram Production Using GIS Based Analytical Hierarchy Process in Kitui County, Kenya

Abstract: The aim of this study was to develop a suitability model for Green gram production in Kitui County using GIS-based multi-criteria evaluation. Soil and topography were chosen as the main criteria for analysis and 6 sub criteria (soil texture, depth, pH, cation exchange capacity drainage and slope). The criteria were selected based on crop experts' knowledge and available Green gram requirements literature. The criteria maps were reclassified into 4 suitability levels Highly (S1), Moderately (S2), Marginally (S3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…For evaluating the land suitability of pulse crop (green gram), eleven criteria (Table 1) are considered which belong mostly to topography (slope and elevation), climate (rainfall, land surface temperature), land use land cover (LULC), and soil characteristics (topsoil texture, soil drainage, soil salinity, soil pH, soil depth, and inundation land type) based on a relevant literature review [42][43][44][45][46] and the opinions of experts like agriculturists, agronomists, and government personnel from the agriculture ministry.…”
Section: Multicriteria Evaluation Of the Land Suitability Analysismentioning
confidence: 99%
“…For evaluating the land suitability of pulse crop (green gram), eleven criteria (Table 1) are considered which belong mostly to topography (slope and elevation), climate (rainfall, land surface temperature), land use land cover (LULC), and soil characteristics (topsoil texture, soil drainage, soil salinity, soil pH, soil depth, and inundation land type) based on a relevant literature review [42][43][44][45][46] and the opinions of experts like agriculturists, agronomists, and government personnel from the agriculture ministry.…”
Section: Multicriteria Evaluation Of the Land Suitability Analysismentioning
confidence: 99%
“…Agriculture is likely to be the most vulnerable sector to the changing climate with stress on subsistence farming in the tropical region, as smallholder farmers lack sufficient resources to acclimatize to climate change (Eriksen et al, 2005;Adhikari et al, 2015). Understanding the spatial variability of climate parameters can help fight hunger and poverty and improve the wellbeing of smallholder farmers by improving their management of natural resources for agricultural production (Mugo et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Mugo et al [14] found some areas in Kitui County, an ASAL region in Kenya, suitable for production in terms of climate. There is, however, a lack of knowledge on whether other ASAL areas in Kenya are currently suitable for green gram production, and how climate change will affect their current suitability.…”
Section: Introductionmentioning
confidence: 99%